Production of Hesperetin Using a Covalently Multipoint Immobilized Diglycosidase from Acremonium sp. DSM24697 - Piñuel, María L. (2013)
Fil: Piñuel, María L. Universidad Nacional de La Pampa. Facultad Ciencias Exactas y Naturales; Argentina